A new analytical model of ploughing friction for arbitrary grit shape on any unflat surface. Issue 7 (1st April 2022) - Feng, Junyuan; Huang, Xiaofang; Meng, Fanning; Bu, Yingbin; Wan, Zhenping; Yang, Shu; Zhang, Zhenyu
Abstract: To gain better knowledge of the grinding process especially the grinding force and efficiency, the friction characteristics between workpiece and abrasive grains has been investigated extensively. However, the calculation of coefficient of friction (COF) in previous studies is limited to indenters with optimized shapes, e.g. pyramidal shape from Berkovich and Vickers indenter or conical shape from conical indenter. In the kinematic simulation of grinding, the applicability of previous models in estimating the contact area and COF is limited due to the very irregular grit shapes of the grinding product. In this study, a new model for calculating the COF for scratches by arbitrary grit shape on any unflat surface is proposed, which only involves the elastic recovery ratio, the pile-up ratio, the grit profile and the workpiece surface profile prior to scratch. To verify the model, single scratch tests under two different shape indenter were conducted on a Nanoindenter. The model is then used to analyze the influence of indenter tip shape on the COF by applying it to a few typical shapes of grinding grits. Finally, good agreement was found on the variation trend of the COF in double scratch tests under different separation distances.